2023
DOI: 10.1002/smll.202204031
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of GSDMD‐N mRNA by Engineered Extracellular Vesicles Induces Pyroptosis for Enhanced Immunotherapy

Abstract: Pyroptosis is a newly discovered inflammatory form of programmed cell death, which promotes systemic immune response in cancer immunotherapy. GSDMD is one of the key molecules executing pyroptosis, while therapeutical delivery of GSDMD to tumor cells is of great challenge. In this study, an extracellular vesicles‐based GSDMD‐N mRNA delivery system (namely EVTx) is developed for enhanced cancer immunotherapy, with GSDMD‐N mRNA encapsulated inside, Ce6 (Chlorin e6 (Ce6), a hydrophilic sensitizer) incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…[ 10 ] Shi et al developed a synthetic multivalent antibodies retargeted exosome (SMART‐Exo) displaying both anti‐human CD3 and anti‐human HER2 antibodies, and the SMART‐Exos dually targeting T cell CD3 and breast cancer‐associated HER2 receptors for immune‐activation. [ 11 ] EVs were also used to pack GSDMD‐N mRNA to induce cell pyroptosis in HER + breast cancer, [ 26 ] in turn the immunogenic pyroptosis induced a robust immunotherapy. Moreover, immune cell‐derived EVs and tumor cell‐derived EVs were used as antigen sources or adjuvant carriers to boost anti‐cancer immune response.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Shi et al developed a synthetic multivalent antibodies retargeted exosome (SMART‐Exo) displaying both anti‐human CD3 and anti‐human HER2 antibodies, and the SMART‐Exos dually targeting T cell CD3 and breast cancer‐associated HER2 receptors for immune‐activation. [ 11 ] EVs were also used to pack GSDMD‐N mRNA to induce cell pyroptosis in HER + breast cancer, [ 26 ] in turn the immunogenic pyroptosis induced a robust immunotherapy. Moreover, immune cell‐derived EVs and tumor cell‐derived EVs were used as antigen sources or adjuvant carriers to boost anti‐cancer immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Since puromycin inhibits translation, untranslated GSDMD-N mRNA can be easily sorted into exosomes. Through this process, they successfully loaded GSDMD-N mRNA into exosomes 68 . However, loading mRNA into nanocarriers is still challenging due to the instability and large size of the mRNA, which complicates packaging and controlled release.…”
Section: Exosomes For Therapeutic Agent Deliverymentioning
confidence: 99%
“…Although an effective technique to deliver GSDMD protein to cancer cells presents a challenge, EV-mediated delivery of functional GSDMD mRNA to cancer cells offers a promising solution. EVs expressing anti-HER2 + antibodies were used in a recent study to deliver GSDMD mRNA to HER2 + cancer cells in a HER2 overexpressing mouse model resulting in induced pyroptosis and a tumor immune response that significantly suppressed tumor growth and prolonged mouse survival compared to control mice that were treated with either PBS or unloaded EVs ( Figure 7 A-B ) 121 . This study demonstrated the feasibility of using EVs to deliver exogenous mRNA to tumors to induce tumor immune response to treat HER2 + breast cancer, setting the stage for engineered EVs to be used for other cancer immunotherapy targets.…”
Section: Extracellular Vesicles As Therapeutic Carriers Of Mrnamentioning
confidence: 99%